Christmas at the island hotel : a novel - Colgan, Jenny (William Morrow, an imprint of HarperCollinsPublishers, 2020)
Sent by his privileged family to learn how the less fortunate earn their living, a duke's son takes a job at a new Murian hotel while falling unexpectedly in love with a hardworking young waitress.